2013
DOI: 10.3389/fcimb.2012.00168
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of damage-associated molecular patterns related to nucleic acids during inflammation and vaccination

Abstract: All mammalian cells are equipped with large numbers of sensors for protection from various sorts of invaders, who, in turn, are equipped with molecules containing pathogen-associated molecular patterns (PAMPs). Once these sensors recognize non-self antigens containing PAMPs, various physiological responses including inflammation are induced to eliminate the pathogens. However, the host sometimes suffers from chronic infection or continuous injuries, resulting in production of self-molecules containing damage-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 137 publications
(152 reference statements)
1
104
0
Order By: Relevance
“…When cells are attacked by exogenous pathogens, host cellular receptors recognize pathogen-associated molecular patterns (PAMPs), small molecular motifs conserved among microbes. In many cases, pathogen elimination requires the damage-associated molecular patterns (DAMPs) that include endogenous intracellular molecules released by activated or necrotic cells [37]. PAMPs such as lipopolysaccharide (LPS) can induce the synthesis of pro-inflammatory cytokines such as pro-interleukin (IL)-1β [38], and its release occurs after NALP-3 inflammasome complex activation [39].…”
Section: Relationship Between P2x 7 R and Fibrosismentioning
confidence: 99%
“…When cells are attacked by exogenous pathogens, host cellular receptors recognize pathogen-associated molecular patterns (PAMPs), small molecular motifs conserved among microbes. In many cases, pathogen elimination requires the damage-associated molecular patterns (DAMPs) that include endogenous intracellular molecules released by activated or necrotic cells [37]. PAMPs such as lipopolysaccharide (LPS) can induce the synthesis of pro-inflammatory cytokines such as pro-interleukin (IL)-1β [38], and its release occurs after NALP-3 inflammasome complex activation [39].…”
Section: Relationship Between P2x 7 R and Fibrosismentioning
confidence: 99%
“…Histones, nucleic acids, HMBG1 (non-histone DNA binding protein from chromatin) etc belong to the class of DAMPs (Damageassociated molecular pattern molecules). DAMPs are associated with inflammatory response in non-infectious immune response [47,48]. It is reported that the DAMPs leads to massive inflammatory reaction and also promotes further production of DAMPs, thus a cyclic reaction [47].…”
Section: Discussionmentioning
confidence: 99%
“…DAMPs are associated with inflammatory response in non-infectious immune response [47,48]. It is reported that the DAMPs leads to massive inflammatory reaction and also promotes further production of DAMPs, thus a cyclic reaction [47]. Histones and non-degraded DNA accumulated in macrophages leads to the production of high levels of type 1 interferons (IFN) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the endosymbiotic theory suggests that mitochondria originate from freeliving bacteria, and as such, mitochondria have their own DNA (mtDNA). Nuclear DNA (nDNA), RNA, and mtDNA can bind to TLRs and as such stimulate the production of proinflammatory cytokines (55,56).…”
Section: Nucleic Acidsmentioning
confidence: 99%